Modification of subjectivity in historical movement of mankind - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article is devoted to comprehension of the problem of subjectivity as a philosophical and religious problem. There are three periods in the development of the concept of "subjectivity", as well as revealing the existing approaches to this problem in modern philosophy.